Nordatlantik I - 1.1 Die Bedeutung des Süßwasserhaushalts für die zukünftige Entwicklung der thermohalinen Zirkulation; 1.2 Rolle des äquatorialen Atlantiks als Schlüsselregion für Klimaschwankungen im atlantischen Raum; 2.2 Schwankungen der tiefen Randstromzirkulation am Ausgang des Labradorsee; 3.2 Schwankungen der thermohalinen Zirkulation in hoch auflösenden Modellen : Schlussbericht - Böning, Claus W.; Eden, Carsten; Latif, Mojib; Stramma, Lothar; Brandt, Peter; Fischer, Jürgen; Oschlies, Andreas; Visbeck, Martin (BMBF / IFM-GEOMAR, 2010)
Visible results were obtained by the working groups in Kiel on the first four aspects of the project, resulting in improvements of the quantitative knowledge of key processes and key regions in the Atlantic Ocean. New ocean and coupled ocean-atmosphere models were analyzed with regard to seasonal and decadal climate changes, as well as optimization techniques. In addition, the influence of circulation variability on oceanic CO2 uptake was investigated. Intense field studies were carried out successfully in two regions: The measurements obtained in the equatorial Atlantic serve as the basis for a better understanding of the role of the tropical Atlantic for climate fluctuations in the Atlantic in general, and also provide predictability indicators for seasonal forecasts. The second focal area of field work was the southern region of the Labrador Sea near 53°N where different components of the North Atlantic Deep Water merge to form the deep western boundary current (DWBC). Here a mooring array has been deployed for the past 13 years to monitor this branch of the thermohaline circulation exiting the Labrador Sea. In collaboration with other national and international large-scale observations (ship-based measurements, Argo floats, etc.) and modeling efforts, the field work carried out by the Kiel working groups provides a significant contribution toward a sustainable regional ocean-climate analysis system.